Lateral Alveolar Ridge Augmentation with Autogenous Tooth Block Graft Compared with Autogenous Bone Block Graft: a Systematic Review - Thomas Starch-Jensen; Julie Vitenson; Daniel Deluiz; Kimie Bols Østergaard; Eduardo Muniz Barretto Tinoco (Stilus Optimus, 2022)
Objectives: The objective of the present systematic review was to evaluate the current knowledge of implant treatment outcome following lateral alveolar ridge augmentation with autogenous tooth block graft compared with autogenous bone block graft prior to implant placement. Material and Methods: MEDLINE (PubMed), Embase and Cochrane Library search in combination with hand-search of relevant journals was conducted including human studies published in English through December 20, 2021. Comparative and non-comparative studies assessing lateral alveolar ridge augmentation with autogenous tooth block graft were included. Quality and risk-of-bias assessment were evaluated by Cochrane risk of bias tool, Newcastle-Ottawa Scale and GRADE system. Results: One comparative study characterized by low grade and two non-comparative studies fulfilled the inclusion criteria. No significant difference in short-term implant survival, health status of the peri-implant tissue or frequency of complications between the two treatment modalities was observed. Postoperative dimensional changes of the alveolar ridge width were significant diminished with tooth block compared with bone block (P = 0.0029). Consequently, the gain in alveolar ridge width was significantly higher with tooth block, after 26 weeks (P = 0.014). However, a higher frequency of short-term peri-implant mucositis was observed with tooth block. Conclusions: Lateral alveolar ridge augmentation with tooth block seems to be a suitable alternative to bone block. However, results of the present systematic review are based on short-term studies involving small patient samples. Further long-term randomized controlled trials are therefore needed before definite conclusions can be provided about the beneficial use of tooth block compared with bone block.